OCORRÊNCIA DE Anaplasma spp. E Babesia spp. EM BOVINOS LEITEIROS DE GUARAPUAVA – PR E REGIÃO - CHICALSKI, TATIANA BISCHOF (2023)
This study aimed to verify the occurrence of blood parasites Anaplasma platys and Babesia spp. by the polymerase chain reaction (PCR) method in Guarapuava/PR and region. Were selected 76 dairy cattle farms located in the municipalities of Guarapuava, Prudentópolis, Turvo, Pinhão, Reserva do Iguaçu, Foz do Jordão, Candói, Cantagalo, Campina do Simão, Boaventura de São Roque, Marquinho and Goioxim, which belong to the south-central region of Paraná. A total of 509 blood samples were collected for PCR, and in 244 samples, erythrograms and plateletograms were performed, and 76 epidemiological questionnaires were answered by the farmers. The PCR detected 109 cattle positive for Babesia spp. (21.41%), 11 positives for Anaplasma platys (2.16%) and 3 animals with coinfection for Babesia spp. and A. platys (0.58%). The results of the erythrograms showed anemia in 8.6% (21/244), 18 animals were positive for Babesia spp. and 3 positives for A. platys, and the animals that presented coinfection did not present anemia. The questionnaires pointed out that 47% of the surveyed properties were semi-intensive dairy farms (36/76) and 49% produced up to 50 L of milk per day (37/76); 57.89% reported the occurrence of cattle tick fever, and 81.59% (61/76) described the presence of ticks in dairy animals. This study reports for the first time the occurrence of A. platys in dairy herds in Brazil, as well as the coinfection of A. platys and Babesia spp.